Defining livestock breeds in the context of community-based management of farm animal genetic resources - Rege, J.E.O. (Food and Agriculture Organization of the United Nations, 2001)
The concept of a breed, in which all members have a pedigree tracing their ancestry, was developed primarily in Western Europe during the eighteenth century. Today, in the developed world, breeds are recognized as distinct intra-specific groups, the members of which share particular characteristics, which distinguish them from other such groups, and formal organizations usually exist for each breed or breed group. The term breed as a formal designation has little meaning outside areas of western influence, where pedigree recording is often non existent. Nonetheless, even under these circumstances, there exist strains or `types' which owe their continuing distinct identity to a combination of traditional 'breeding objectives' and geographical and/or cultural separation by communities which own them. This paper discusses the concept of livestock breeds in the context of community-based management of farm animal genetic resources in developing countries. It is pointed out that there exist elaborate traditional systems of population identification by local communities, and that these `uniquely identified and named' populations, the equivalent of `breeds' in western agriculture, are important basic units of diversity assessment and conservation. In many instances, the local environment, culture and values of communities are reflected in the key traits and/or functions of the livestock `breeds'. These may range from such complex traits as adaptation to local environmental stresses, to functions such as traction or products such as milk or wool and simple traits such as presence and size of horns or humps. Behind these traits are the breeding practices and other indigenous knowledge systems that have been applied for the maintenance of these populations, and the genetic diversity that they represent. The paper concludes that the concept of breed or equivalent concepts within species serve an important purpose in that it links products/functions to a group of animals that share common genetic background. To the extent that conservation of agricultural diversity need to be linked to utilisation, and the fact that the concept of breeds as aggregate or `package' of traits is a manifestation of the environment and community values and goals, breeds represent the single most important unit of analysis in the context of conservation and use of livestock diversity, and must be considered as such in developing strategies for the sustainable management of livestock diversity at the community level.